Fiscal Policy of the Federal Government: Between a Debt Brake and Tax Increases - Matthias Diermeier; Michael Hüther; Thomas Obst (Wirtschaftsdienst)
Abstract The 2021 election campaign in Germany has revealed substantial demands on the federal budget in the coming legislative period. Some coalition partners, however, have rejected a reform of the debt brake and simultaneously promise tax cuts. A ‘burden forecast’ for the next four years indicates that these campaign promises will triple expenditures from 37 to 105.1 billion euro and will exclude urgent investments to modernise public infrastructure, cope with climate change and tackle digital transformation. With the debt brake maxed out, the financing of up to 263 billion euro remains up in the air. Keeping the debt brake without increasing taxes would be like trying to ‘square the circle’.